Diseño de un modelo de gestión por procesos para el área de crédito de la Cooperativa de Ahorro y Crédito “Chone Limitada - Salazar Castillo, María Gabriela (2014)
The origin of the cooperative in Ecuador emerged in the last decade of the nineteenth century, where the purpose of it was to create artisan mutual aid organizations. Taking on this value , and the current improvements in the financial sector through the Ley de Economía Popular y Solidaria, innovation is essential processes through the design of a management model that allows them to standardize , benefiting the standard of living of its members, and hence the good life . This thesis is developed in a real scenario: the Cooperativa de Ahorro y Crédito “ChoneLimitada”; analyzing the credit process in this state, it is essential to establish improvements to expedite and streamline the process itself. This optimization involves implementing a credit line of easy access, resulting in improved customer response times. This facility will be monitored through a model proposed indicators which disclose the conduct thereof and therefore compliance with the financial institution.